Gastrointestinal bleeding caused by jejunal angiosarcoma: A case report - Hui, Yang-Yang (World J Clin Cases, 2020)
BACKGROUND: Angiosarcoma is a rare disease with a poor prognosis. Its occurrence in the small intestine is low, and gastrointestinal bleeding caused by small intestinal angiosarcoma is unusual. CASE SUMMARY: Here, we report the case of a 57-year-old man who presented with hematochezia for 1 mo. The patient had a medical history of chronic viral hepatitis B for 15 years. The causes of gastrointestinal bleeding were initially diagnosed as esophagogastric variceal bleeding or portal hypertensive gastropathy before endoscopy. However, after a complicated diagnostic and therapeutic process, including gastroendoscopy, colonoscopy, contrast-enhanced computed tomographic (CT), positron emission computed tomography/CT, capsule endoscopy, and pathological and immunohistochemical examinations, small intestinal angiosarcoma was diagnosed. Arrest of bleeding was achieved after surgical treatment. Furthermore, the patient had lung cancer with bone and adrenal metastases. At the follow-up 10 mo after the operation, the patient was alive. CONCLUSION: Gastroenterologists should maintain strong vigilance to small intestinal angiosarcoma, which is necessary for the early identification of this infrequent but fatal disease.